2007
DOI: 10.1007/s00775-007-0276-0
|View full text |Cite
|
Sign up to set email alerts
|

XH/π interactions with the π system of porphyrin ring in porphyrin-containing proteins

Abstract: Searching structures of porphyrin-containing proteins from the Protein Data Bank revealed that the pi system of every porphyrin ring is involved in XH/pi interactions, with most of the porphyrins having several interactions. Both five-membered pyrrole rings and six-membered chelate rings are involved in XH/pi interactions; the number of interactions with five-membered rings is larger than the number of interactions with six-membered rings. We found interactions with C-H and N-H groups as hydrogen-atom donors; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 66 publications
0
23
0
Order By: Relevance
“…In order to find out the importance of different noncovalent interactions of the porphyrin ring in proteins, in our previous work we studied the conservation of the residues involved in the interactions [23]. The data about the average conservation scores are calculated for four groups of amino acids in binding pocket; for the amino acids involved in the XH/ (X = N, C) interactions with porphyrin ring, in hydrogen bonds, in hydrophobic interactions, and for the amino acids that are not involved in any type of the interactions with the porphyrin [23].…”
Section: Conservation Score Of Amino Acid Residuesmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to find out the importance of different noncovalent interactions of the porphyrin ring in proteins, in our previous work we studied the conservation of the residues involved in the interactions [23]. The data about the average conservation scores are calculated for four groups of amino acids in binding pocket; for the amino acids involved in the XH/ (X = N, C) interactions with porphyrin ring, in hydrogen bonds, in hydrophobic interactions, and for the amino acids that are not involved in any type of the interactions with the porphyrin [23].…”
Section: Conservation Score Of Amino Acid Residuesmentioning
confidence: 99%
“…Searching structures of porphyrincontaining proteins from the Protein Data Bank it was revealed that -system of every porphyrin ring is involved in CH/ interactions and most of the porphyrins are making several interactions. The amino acids involved in the interactions show high conservation score indicating that CH/ interactions play an important role in the porphyrinprotein stability [23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…. .π and stacking interactions of chelate rings [8,[18][19][20][21][22][23][24][25][26][27][28]. Other groups have reported CH.…”
Section: Interactions With π -Systems Of Chelate Ringsmentioning
confidence: 99%
“…These chelate ring π -systems can potentially be involved in CH-π interactions. Such interactions have been identified in the crystal structures of transition-metal complexes [21,22] and in structures of porphyrin-containing proteins [23]. A summary is presented below.…”
Section: Ch π Interactions In Metal-porphyrin Complexesmentioning
confidence: 99%